Cerebral Ischemia-Reperfusion Is Associated With Upregulation of Cofilin-1 in the Motor Cortex - Xu, Ming-Shu; Yin, Lei-Miao; Cheng, Ai-Fang; Zhang, Ying-Jie; Zhang, Di; Tao, Miao-Miao; Deng, Yun-Yi; Ge, Lin-Bao; Shan, Chun-Lei (Frontiers in Cell and Developmental Biology, 2021)
Cerebral ischemia is one of the leading causes of death, although its mortality rate has been decreasing in recent years worldwide. Reperfusion is a critical stage after thrombolysis, accompanied by oxidative stress, excitotoxicity, neuroinflammation, and defects in synapse structure. The process is closely related to the dephosphorylation of actin binding proteins (e.g., cofilin-1) by specific phosphatases. Although studies of the molecular mechanisms of the actin cytoskeleton have been ongoing for decades, limited studies have directly investigated reperfusion-induced reorganization of actin binding protein, and little is known about the gene expression of actin binding proteins. The exact mechanism is still uncertain. The motor cortex is very important to save nerve function; therefore, we chose the penumbra to study the relationship between cerebral ischemia-reperfusion and actin binding protein. After middle cerebral artery occlusion, the cerebral blood flow of the motor cortex was decreased, the mRNA of actin binding proteins (such as cofilin-1) was upregulated, and the cofilin-1 protein level was increased in the penumbra of the motor cortex. The change in actin binding protein expression appears at the same time as gait imbalance. It is suggested that actin-binding proteins, especially cofilin-1, may further affect motor cortex function. This result provides a potential mechanism for understanding cerebral ischemia-reperfusion.